Reproduction of gender-based symbolic violence in the weaving industry: A case study of Ikat Weaving in Kediri - Diah Handayani; Aniello Iannone (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2025)
Gender-based symbolic violence in weaving industries is reproduced through informal work systems, wage disparities, and age hierarchies normalized by local culture, producing inequalities perceived as natural in informal labor contexts. This study aims to analyze symbolic violence in the Kediri ikat weaving industry across three domains working hours, wage structures, and age disparities that reproduce domination, inequality, and worker compliance. This study employed a qualitative approach using a case study design in three weaving centers in Kediri, involving 12 participants. Data were collected through interviews, observation, and documentation, and were analyzed thematically with triangulation for validation. This study identifies three forms of symbolic violence: (1) working-time exploitation through the putting-out system, subtle threats, rights removal, and dominant habitus; (2) wage inequality through gender-based differentiation, devaluation of women’s labor, and elimination of bonuses; and (3) age-based inequality through uniform wages, internalized resignation among elderly workers, and bonus allocation based on proximity to power structures. This study concludes that symbolic violence in working hours, wages, and age within the Kediri weaving industry is naturalized as normal practice, thereby sustaining structural inequalities that persist without resistance or critical awareness. This study contributes to the extension of Bourdieu’s theory by revealing the reproduction of symbolic violence in weaving labor and offers practical implications in the form of wage transparency, recognition of skills equality, and fair bonus distribution.